National unity at the university level: An exploratory study at the University of Malaya / Chang Lee Wei - Chang, Lee Wei (2016)
Unity has always been the main theme of Malaysia since its independence in 1957. However, the increasingly arose tensions from its fount of diversity and from the politicization of race and religion have always reminded us to rethink and assess the current scenario and situation of national unity in Malaysia. The school has always been appointed as one of the most important places where national unity may be nurtured. However, to focus only on schools, it would only be tinkering at the edges of the issue of national unity. University, a place where future leaders are being produced should as well be encouraged to play a role in nurturing national unity. Contemporary university students are the backbone of the modernization drive; they are the hope of the country’s future development and their perceptions and attitudes on the issue of national unity are directly affecting the entire society and the nation. Therefore, to strengthen ethnic unity of contemporary university students is also very important. Within the framework of national unity, this research aimed at examining the efforts done and challenges in nurturing national unity at the university level. It also examined the possibility of implementing/practicing dialogue programme as a way to foster national unity at the university level. Mixed mode method has been used to study the perceptions of various university stakeholders. 420 survey form were distributed and collected from respondents. There are more than 99% of respondents aware the importance of national unity both the university level and national level, however, there are more than 80% of the respondents supported that at the same time, there are also negative issues on national unity at the university level (university students are not in favour of nurturing national unity at the university level). This indicated the efforts of promoting/nurturing national unity at the university level are still not sufficient or perhaps a new method (practice of dialogue) of nurturing national unity among the university students should iv be introduced. Feedbacks from interviewees also indicated that a more interactive and proactive way of teaching during the TITAS/Ethnic Relations Courses should be encouraged so that the good policies/concepts/ideology introduced to promote national unity could be fully reflected via practices